Effect Of Dragon Fruit Peel Flour (Hylocereus Sp.) In Complete Feed On Characteristics Of Rumen Fermentation In Goat (Journal of Pharmaceutical Negative Results, 2023)
Dragon fruit peel is an agricultural waste that contains potential nutrients so that it can be used as an alternative ingredient for making complete feed. The purpose of this study was to examine the effect of giving complete feed containing dragon fruit peel flour (Hylocereus sp.) on rumen fermentation characteristics (pH,N-NH3,VFA) in goats. This study used 12 male goats based on a randomized block design with 3 treatments and 4 groups. The treatment consisted of complete feed with 50% corn flour and without dragon fruit peel flour (P1), complete feed with 45% corn flour and 5% dragon fruit skin flour (P2) and complete feed with 40% corn flour and dragon fruit skin flour. 10% (P3). The results showed that complete feed treatment with the addition of dragon fruit peel flour had no significant effect (P>0.05) on rumen fermentation characteristics (pH,N-NH3,VFA). The mean pH values ranged from 6.80-7.22, N-NH3 levels ranged from 4.76-7.85 (mM) and VFA levels ranged from 28.46-40.48 (mM). It was concluded that complete feed with the addition of dragon fruit peel flour at a level of 10% produced optimal values for rumen fermentation characteristics based on pH values and ammonia levels (N-NH3).